The Contribution of Shaikh Mustafa Hussain’s Thought to Theology of Community in Purba Baru Village - Purnama Lubis (Program Doktor Akidah dan Filsafat Islam, 2019)
The main issue in this research is how the impact of thought SyekhMusthafa Husein on the development of theology society Purba BaruVillage. This research is the Influence Study concept of a character whois qualitative, which is an interpretive and naturalistic analyst on thephenomenon under research. The approach to theology's themes is asefforts approach religious societies by using the framework of theologyor science of Godhead with a point of reference patterns SyekhMusthafa Husein theology. The theology society of Purba Baru isAsh‘ariyah and Maturidiyah according to the theology developed bySheikh Hussein Mustahafa called understand Ahlu Sunnah wa al-Jama’ah, theology Ahl Sunnah wa al-Jama‘ah patterned rational,rationality is reflected in the used of public understanding reality laws ofreason and daily community life, and understanding of the variousfundamental themes of theology who asked the communities in PurbaBaru Village Lembah Sorik Marapai Subdistrict.